Protamines and spermatogenesis in Drosophila and Homo sapiens : A comparative analysis. - Kanippayoor, R.L.; Alpern, J.H.; Moehring, A.J. (Spermatogenesis, 2013)
The production of mature and motile sperm is a detailed process that utilizes many molecular players to ensure the faithful execution of spermatogenesis. In most species that have been examined, spermatogenesis begins with a single cell that undergoes dramatic transformation, culminating with the hypercompaction of DNA into the sperm head by replacing histones with protamines. Precise execution of the stages of spermatogenesis results in the production of motile sperm. While comparative analyses have been used to identify similarities and differences in spermatogenesis between species, the focus has primarily been on vertebrate spermatogenesis, particularly mammals. To understand the evolutionary basis of spermatogenetic variation, however, a more comprehensive comparison is needed. In this review, we examine spermatogenesis and the final packaging of DNA into the sperm head in the insect Drosophila melanogaster and compare it to spermatogenesis in Homo sapiens.